Non-alcoholic fatty liver disease (NAFLD) in non-obese individuals. Issue 6 (13th December 2019) - Phipps, Meaghan; Wattacheril, Julia
Abstract : Individuals with non-alcoholic fatty liver disease (NAFLD) who lack classical risk factors also have the ability to develop nonalcoholic steatohepatitis (NASH) and progression to more advanced liver disease. The pathophysiology and risk factors for the development of NAFLD in non-obese persons are not fully understood but seem to be closely related to insulin resistance, atherogenic dyslipidaemia and alterations in body composition, with some patients harbouring predisposing genetic polymorphisms. In normal-weight individuals, also called 'lean', there is limited potential for effective lifestyle change in disease management. Additionally, biological mechanisms underlying the development of NASH in non-obese individuals may reveal novel targets for intervention. In this review, the authors discuss the clinical, histological and genetic features and risk factors for non-obese NAFLD and highlight gaps in knowledge and areas for future research.